Are COVID Fatalities in the US Higher Than in the EU, and If So, Why? - Ainoa Aparicio Fenoll; Shoshana Grossbard (Institute of Labor Economics (IZA), 2020)
The COVID crisis has severely hit both the United States and the European Union. Even though they are the wealthiest regions in the world, they differ substantially in economic performance, demographic characteristics, type of government, health systems, and measures undertaken to counteract COVID. We construct comparable measures of the incidence of the COVID crisis and find that US states had more COVID-related deaths than EU countries. When taking account of demographic, economic, and political factors (but not health-policy related factors) we find that fatalities at 100 days since onset are 1.3 % higher in a US state than in an EU country. The US/EU gap disappears when we take account of health-policy related factors. Differences in number of beds per capita, number of tests, and early lockdown measures help explain the higher impact of COVID on US fatalities measured either 50 or 100 days after the epidemic started in a nation/state.
Keywords: I18; J1; J18; 330; COVID-19; mortality; Europe; US; health policy